Pertumbuhan dan Produksi Dua Jenis Sawi Menggunakan Perbedaan Nutrisi Secara Aeroponik - Isnaeni, Selvy; Nasrudin, N (Journal Galung Tropika, 2021)
Consumer demand for mustard needs in Indonesia is increasing. Efforts to produce mustard greens use an aeroponic system to utilize nutrients in dosage and type correctly. The study aimed to determine the proper type of nutrition for the growth and production of two mustard greens in an aeroponic system. This study used a completely randomized design with two factors. The first factor is the type of mustard which consists of two levels, namely pakcoy and pagoda. The second factor to consider is the nutrition applied at three different levels: AB mix, liquid organic fertilizer, and foliar fertilizer. Mustard greens grew and produced significantly differently when grown in an aeroponics system. Other nutrients greatly affected all observed variables, including plant height, leaf number, leaf color, root length, fresh plant weight, and dry plant weight. The use of pakcoy mustard provides the best growth and production of mustard greens compared to pagoda-type mustard. Giving AB mix nutrition to mustard greens can provide the best growth and production compared to nutrition from liquid organic fertilizers and foliar fertilizers. The AB mix nutritional treatment with pakcoy mustard produced the best results in plant height, leaf number, wet weight, dry weight, and root length. AB mix nutritional showing the best leaf color variable with pagoda mustard greens.